Draft Annual Plan 1980-81 Government of Punjab - Planning Commission (Planning Commission, 1980)
The overall strategy and objectives of the Draft Annual Plan 1980-81 are in conformity with those laid down in the Sixth Five Year Plan 1978—83 : Framework. the objective and strategy have been derived from the basic goal of developing Punjab into a Model State during the next nine years. The main elements of this strategy are : Accelerated growth. Diversification of the economy. Fuller employment.
Government of Punjab, Department of Planning